Wide Band Open Ended Air Gap RLSA Antenna at 5.8GHz Frequency Band - Mohd Ibrahim, Imran (IEEE, 2012)
RLSA antenna is a popular candidate for the application of Point to Point Microwave Link. This is due to its capability of carrying high speed signal. RLSA prototypes has been designed and developed at the frequency range of 5725 – 5875 MHz by few researchers. The classic design was using enclose air gap as a separator between radiation surface and ground plane. Then, the slow wave material has been used in the RLSA cavity. The implementation of FR4 board to RLSA design recently has allowed a reconfigurable and beam shaping of radiation pattern.[5]. The open air gap cavity structure normally implemented in broadband planar antenna.[6] This structure normally provide a wide bandwidth and good return loss on the desired frequency. Therefore, an investigation of this technique and hybrid with FR4 board as a cavity material will be very interesting due to condition of easy to manufacture, lighter the antenna weight and durable.[7]